Characterization of anatomical features, developmental roadmaps, and key genes of bamboo leaf epidermis. Issue 6 (17th November 2022) - Jiang, Jiawen; Gao, Zhipeng; Xiang, Yu; Guo, Lin; Zhang, Chuzheng; Que, Feng; Yu, Fen; Wei, Qiang
Abstract: The exact developmental roadmaps of bamboo leaf epidermis and the regulating genes are largely unknown. In this study, we comprehensively investigated the morphological features of the leaf epidermis of bamboo, Pseudosasa japonica . We also established the developmental roadmaps of the abaxial epidermis along the linearly growing leaf. A variant of P . japonica, P . japonica var. tsutsumiana, with smaller stomata and higher stomata density, was identified. Further analysis revealed that the higher stomata density of the variant was due to the abnormal increase in stomata columns within the single stomata band. This abnormal development of stomata bands was observed as early as the guard mother cell stage in the leaf division zone (DZ). Interestingly, the developmental pattern of the single stomata was similar in P . japonica and the variant. Molecular data showed that PjDLT ( D warf and L ow T illering ) was significantly downregulated in leaves DZ of the variant. Overexpression of PjDLT in Arabidopsis and rice results in smaller plants with lower stomata density, whereas downregulation or mutation of OsDLT results in increased stomata density. Our results highlight the morphological features and developmental schedule of the leaf epidermis of bamboo and provide evidence that DLT plays an important role in regulating stomata in bamboo and rice.